Personality profiles and stress-coping strategies of Slovenian military pilots - Maja Meško; Damir Karpljuk; Mateja Videmšek; Iztok Podbregar (Psihološka Obzorja, 2009)
The performance of a pilot also depends on the pilot's personality profile and their stresscoping style. In our study we aimed to analyze, by means of the Big Five Questionnaire (BFQ) and the Coping Responses Inventory (CRI), the personality profiles, stress-coping strategies and the relationship between them among Slovenian military pilots. The study involved 120 respondents: 30 of whom were military pilots in the experimental group, while the other 90 were in the control groups. The control groups included sport pilots, the general population and soldiers with no involvement in aviation. The members of the control group were selected with regard to the characteristics of the experimental group members, so that both groups were equivalent in terms of relevant factors (e.g. gender, age, health state, level of education etc), thus participating in a study of equivalent pairs. A statistical analysis identified statistically significant differences between the groups in the following BFQ dimensions: energy, conscientiousness and emotional stability; in the dimensions of CRI 'cognitive avoidance' (cognitive effort to avoid realistic consideration of a problem); and 'emotional discharge or emptying' (behavioural attempts to alleviate tension by venting negative emotions). Results revealed that certain personality characteristics were differentially and significantly related to specific stress coping strategies adopted by military pilots.